LOST OR OPPORTUNITY: ON CITY'S LEFTOVER SPACES - Unur, Nihan Gurel; Onal, Feride (STEF92 TECHNOLOGY LTD, 2016)
Urban voids are the left-over spaces of the city that have been emerged in various forms due to reasons such as changing economic, social, functional, technological conditions, environmental issues, planning and legal disputes, urban decay and further on. They differ from traditionally designed urban void, usually come up as results of unplanned changes in the city. Urban voids are disused, underused spaces without a clear definition, usually defined as lost spaces of the city and identified as undesired urban situation. Negative conceptions emphasize economic, social, spatial deterioration they represent in urban fabric. Urban voids are also discussed with concepts such as terrain vague, spaces of uncertainty etc. which emphasize the openness and the potential they offer for spontaneous, bottom-up, daily practices and for future public uses. Within this scope the city of Istanbul has witnessed periods of decline and abandonment and leftover spaces have emerged in city's fabric. In 1950-1970 with rapid urbanization, increase in urban population urban space began to change radically. In 2000's with accelerated neoliberal urban policies, urban agenda is transforming urban space into shopping malls, gated communities etc. through large-scale projects. Existing urban voids in inner-city areas are the primary goal for this never-ending demand for construction. Presently, the city does not have a lot of land left and being challenged by urbanization and densification, which also raises the issue of lack of urban voids. Istanbul which is the densest city in Turkey will have to deal with limited urban space in the future in this sense urban void become a key element in terms of reuse. Kadikoy which is the study area of this paper, located in Asian side of the city. An urban void from Kadikoy that used to be recreational area long time ago became neglected. In this paper negative and positive interpretations about leftover urban spaces and the formation of these spaces in Istanbul's context will be discussed. The transformation of leftover spaces of the city will be studied through reading planning documents, urban projects, aerial survey and by conducting observations.
Keywords: urban voids; Istanbul; leftover space; Kadikoy; Kusdili; Architecture; Art; Social Sciences - Other Topics